Lies the government told you : myth, power, and deception in American history - Napolitano, Andrew P. frey50 (Nashville : Thomas Nelson, 2010)
This explosive work attacks the culture in government that facilitates lying, and it challenges readers to recognize that culture, to confront it, and to be rid of it.
"All men are created equal" -- "All men-- are endowed by their creator with certain inalienable rights" -- "Judges are like umpires" -- "Every vote counts" -- "Congress shall make no law-- abridging the freedom of speech" -- "The right of the people to keep and bear arms shall not be infringed" -- "Your body is your temple" -- "The Federal Reserve shall be controlled by Congress" -- "It's only a temporary government program" -- "I'm from the government, and I'm here to help" -- "We are winning the war on drugs" -- "Everyone is innocent until proven guilty" -- "The Constitution applies in good times and in bad times" -- "Your boys are not going to be sent into any foreign wars" -- "We don't torture" -- "The right of the people to be secure in their persons, houses, papers, and effects, shall not be violated" -- "America has a free market".
Keywords: Constitutional history -- United States; United States -- Politics and government